2006
DOI: 10.1523/jneurosci.0522-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Control of Postsynaptic Density Scaffolds via Actin-Dependent and -Independent Mechanisms

Abstract: Organization and dynamic remodeling of postsynaptic density (PSD) are thought to be critical in postsynaptic signal transduction, but the underlying molecular mechanisms are not well understood. We show here that four major scaffolding molecules, PSD-95, GKAP, Shank, and PSD-Zip45, show distinct instability in total molecular content per synapse. Fluorescence recovery after photobleaching also confirmed their distinct turnover rates. Among the PSD molecules examined, PSD-95 was most stable, but its elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
158
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(182 citation statements)
references
References 61 publications
(78 reference statements)
19
158
1
Order By: Relevance
“…However, we found that the exchange of PSD-95-GFP was slow at the PSD (Fig. S4 B-D), consistent with previous work (22,25,26,31). Preincubation of neurons with jasplakinolide or latrunculin for 15 min did not affect the low rate or extent of PSD-95-GFP fluorescence recovery (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, we found that the exchange of PSD-95-GFP was slow at the PSD (Fig. S4 B-D), consistent with previous work (22,25,26,31). Preincubation of neurons with jasplakinolide or latrunculin for 15 min did not affect the low rate or extent of PSD-95-GFP fluorescence recovery (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Recent live-imaging experiments have focused on the accumulation and dispersal of PSD scaffolds during synaptogenesis or synapse loss (19)(20)(21)(22), the translocation of assembled PSD scaffolds in developing neurons as synapses form (23), or the rates of exchange of various PSD constituents (22,(24)(25)(26). However, the submicron size of the PSD has hindered analysis of its morphology and internal architecture in living neurons.…”
mentioning
confidence: 99%
“…Cytoskeletal filaments are fences themselves and anchor transmembrane proteins, which behave as pickets restricting the diffusion of other molecules on both leaflets of the plasma membrane [the anchored proteinpicket model (Kusumi et al, 2005)]. At synapses, the cytoskeleton is important for the stabilization of the PSD (Kirsch and Betz, 1995;Allison et al, 2000;Kuriu et al, 2006). The actin cytoskeleton also affects the lateral diffusion of GlyRs in spinal cord neurons (Charrier et al, 2006).…”
Section: Confinement Of Synaptic Chtx Depends On F-actinmentioning
confidence: 99%
“…We thus analyzed the effect of actin depolymerization using latrunculin A (3 M) on lipid confinement at synapses. Both gephyrin and Homer1c interact with actinregulating proteins, such as collybistin and profilin in the case of gephyrin (Charrier et al, 2006 and references therein) and cortactin and debrin in the case of Homer (Naisbitt et al, 1999;Kuriu et al, 2006 and references therein). F-actin disruption decreases the size of their clusters (Kirsch and Betz, 1995;Usui et al, 2003;Charrier et al, 2006).…”
Section: Confinement Of Synaptic Chtx Depends On F-actinmentioning
confidence: 99%
“…Presumably neurons must form and then maintain a population of stable contacts with specific synaptic partners in order to ensure proper circuit function, but the molecular mechanisms that underlie this process of synapse stabilization are still poorly understood [1,2]. Further, the ability of a synapse to remain stable is complicated by the recent demonstration that many synaptic proteins are highly dynamic and turn over in both activity-dependent and independent manners [3][4][5][6][7]. Here, we used time-lapse imaging of synapse formation in cultured neocortical neurons to examine the dynamics of association of Ca 2þ /calmodulin-dependent protein kinase II (CaMKII) and postsynaptic density-95 (PSD-95) with sites of axon-dendrite (AD) contact, in order to assess how the localization and amount of these proteins correlates with changes in contact turnover.…”
Section: Introductionmentioning
confidence: 99%